Geometric Thinking Skills of Prospective Mathematics Teachers in the Transformation Geometry Course: Effects and Obstacles - Mirna; Ahmad Fauzan; Yarman; I Made Arnawa; Lufri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Geometry is a compulsory component of mathematics education worldwide; however, it remains one of the most challenging topics for prospective mathematics teachers, particularly transformation geometry. This study aims to examine the level of geometric thinking skills of prospective mathematics teachers based on Van Hiele’s theory, analyze their influence on the transformation geometry learning outcomes, and identify the prospective mathematics teachers’ learning obstacles. A mixed-methods approach research using an explanatory sequential design was employed. Data were collected from 99 prospective mathematics teachers enrolled in a Transformation Geometry course using geometric thinking skills test, transformation geometry learning outcomes test, and learning obstacles open-questionnaire. The data were analyzed using descriptive statistics and simple linear regression. The results indicate that most prospective teachers remain at lower Van Hiele levels, which are below the expected standards for future mathematics teachers. Geometric thinking skills were found to have a significant influence on transformation geometry learning outcomes. Prospective mathematics teachers simultaneously experience ontogenic, epistemological, and didactical obstacles. These findings imply that transformation geometry course should be aligned with students’ geometric thinking levels and supported by appropriate didactic designs. Therefore, future research about developing geometry didactic design based on Van Hiele’s theory in transformation geometry course is essential.